Pengaruh Inflasi, Suku Bunga, dan Kurs Terhadap Return On Asset Pada Bank Umum Syariah - Moh Rizal Kurniawan; Abd. Ghafur; Yeni Kartikawati (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to evaluate the extent of the influence of inflation, interest rates, and exchange rates on Return on Asset (ROA) in Islamic Commercial Banks during the period 2022 to 2024. The approach used in this study is quantitative with a causal associative method, which is designed to test the cause-and-effect relationship between variables. The independent variables analyzed include inflation, interest rates, and exchange rates, while ROA is the dependent variable in this study. The findings from the analysis show that inflation has a positive and significant influence on ROA. In contrast, interest rates and exchange rates show a negative influence on ROA in Islamic Commercial Banks. Simultaneously, the three independent variables are proven to have a significant effect on profitability performance reflected through Return on Asset.